DNA fingerprinting of mycobacterium tuberculosis complex culture isolates collected in Brazil and spotted onto filter paper - Burger, Marion; Raskin, Salmo; Brockelt, Sonia R.; Amthor, Beate; Geiss, Heinrich K.; Haas, Walter (Journal of clinical microbiology, 1998)
The usefulness of filter paper for preservation of bacterial cells was shown by mixed-linker DNA fingerprint analysis ofMycobacterium tuberculosis isolates from 77 Brazilian patients. DNA fingerprints of samples spotted onto filter paper and conventional culture material were identical. Thus, filter paper specimens analyzed by an amplification-based typing method provide a new resource for epidemiological studies of infectious diseases.